OPTIMIZATION IN THE PREPARATION OF THE YBa2Cu307 COMPOUND USING BaC03 AND Ba02 AS REAGENTS - Bustamante D., Angel (2004)
The traditional superconductor YBa2Cu307.¡; (Yl23) has an orthorhombic crystalline structure with spatial group Pmmm and its critica! temperature is 90 K. The literature reports the use of reagent BaC03 for the preparation by the solid state reaction which requires one calcination and two thermal treatments in oxygen flow at 950 oc. In this work we report the comparison in the preparation of Y123 using the Ba02 reagent as another possibility for preparation; in this case we have used only two thermal treatments in oxygen flow at 950 °C; therefore reducing the costs in preparation. The powder XRD pattem of samples prepared with Ba02 confirm a well crystallized phase an the diffraction lines of the main phase can be indexed with an orthorhombic unit cell. The ac susceptibility measurement in the range 5-100 K using a Quantum Design (SQUID) magnetometer for two samples confirms the superconductor behavior with critica! temperature Te91 K. The critica! temperatures for these systems were found taken account the derivatives of the susceptibility curves. Scanning Electron Microscopy (SEM) confirms the good behavior ofthe grains corresponding to both methods.